Motivational Speeches Impact on Undergraduate Students Intrinsic Motivation and Psychological Need Satisfaction - Warsi, Asif Z; Mushtaq, Rabia; Sikapuria, Zahra Karim (Annals of Human and Social Sciences, 2023)
Intrinsic motivation and psychological need satisfaction are essential components of human behavior and psychological well-being. In the context of young adults, these factors play a crucial role in shaping their development, decision-making processes, and overall life satisfaction. The present research study aimed to explore the Impact of motivational speeches on intrinsic motivation and psychological need satisfaction among undergraduate students. A sample of 35 undergraduate students aged between 18 to 25 years for each group were recruited. Participants were randomly assigned to either a motivational speech group or a control group. Pre- and post-intervention assessments were conducted to measure intrinsic motivation and psychological need satisfaction. Results of the pre-test results concludes that there was as such no significant difference among both groups. Whereas, the post-test results concludes that there was a significant difference among both groups regarding understanding of their baseline levels of intrinsic motivation and psychological need satisfaction. Educators, counselors, and mentors should consider incorporating motivational speeches into their programs or interventions aimed at students for enhancing intrinsic motivation and promoting psychological need satisfaction.